2000
DOI: 10.1164/ajrccm.161.2.9904091
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Superoxide Dismutase and Catalase Are Coordinately Expressed in the Alveolar Region in Chronic Interstitial Pneumonias and Granulomatous Diseases of the Lung

Abstract: Free radicals have been suggested to play an important role in the pathogenesis of interstitial lung diseases, the most important of which are chronic interstitial pneumonias such as usual interstitial pneumonia (UIP) and desquamative interstitial pneumonia (DIP) and granulomatous lung diseases such as sarcoidosis. Because manganese superoxide dismutase (MnSOD) and catalase are two important intracellular antioxidant enzymes that probably play a central role in lung defense, the localization and intensity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
54
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 29 publications
6
54
1
Order By: Relevance
“…Only a few studies have investigated MnSOD in human lung diseases. MnSOD is elevated in the inflammatory phases of interstitial lung diseases [14,16]. In contrast, the RNA levels of MnSOD appear to be very similar in the central airways of nonsmokers and smokers [20].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Only a few studies have investigated MnSOD in human lung diseases. MnSOD is elevated in the inflammatory phases of interstitial lung diseases [14,16]. In contrast, the RNA levels of MnSOD appear to be very similar in the central airways of nonsmokers and smokers [20].…”
Section: Discussionmentioning
confidence: 94%
“…Cell-specific expression of MnSOD has been detected in the human lung [14], but its immunoreactivity has not been previously compared at various levels of the airways. Consistent with the previous findings, MnSOD was expressed in central bronchial epithelium, as well as in alveolar macrophages, but the expression was much weaker in peripheral airways than in the bronchial epithelium of large airways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study with the AEC method, which is highly sensitive, confirmed the recent results with the diamino benzidine (DAB) method (Asikainen et al 2001) on the expression of MnSOD already during the 17th gestational week in human bronchial epithelium, developing alveolar epithelium, and alveolar macrophages. In healthy adult human lung, MnSOD is weakly expressed, especially in type II pneumocytes, alveolar macrophages, and bronchiolar epithelial cells (Kinnula et al 1994;Coursin et al 1996;Lakari et al 1998Lakari et al ,2000.…”
Section: Discussionmentioning
confidence: 99%